Failure analysis of directional crossing pipeline and design of a protective device. (August 2016) - Zhang, Jie; Liang, Zheng; Zhang, Han; Feng, Ding; Xia, Chengyu
Abstract: Failure analysis of crossing pipelines in the operation process after the completion of construction was investigated. Dent and collapse are the common failure modes of crossing pipelines in bad geological strata. The deformation processes of dent behaviour and collapse behaviour of crossing pipelines were simulated. The results show that high stress distribution extends along the axial and circumferential directions under the boulder load, and the maximum equivalent plastic strain appears at the centre of the dent. The collapse process of the crossing pipeline can be divided into six phases. The cross-section changes from an oval shape to a "gourd" shape and then to an "8" shape as the external load increases. Before buckling appears, the decrease in the cross-section area of the crossing pipeline is small. However, the cross-section area increases as the surrounding soil pressure increases after buckling appears. When the cross-section shape reaches the "8", the decrease in the cross-section area reaches a maximum value of 88.1%. To reduce the failure probability and improve the service life of the crossing pipeline, a protective device was designed for preventing damage. For the protective device, the dent rate of the protective pipeline decreases as the annulus pressure increases under the action of boulders. However, the dent rate of the crossing pipeline increases as the annulus pressure increases. Under the same stratum movement, the deformation of the crossing pipeline with the protective device is smaller than without the protective device. Therefore, the protective device can effectively protect the crossing pipeline and prevent a collapse accident. The protective device can be effectively used on any parts of the crossing pipeline in different locations due to its simple structure and convenient installation in bad geological strata. Highlights: Dent and collapse processes of the directional crossing pipeline were simulated. Collapse process of the crossing pipeline can be divided into six phases. Cross-section shape changes to "gourd" and "8" shape as the external load increases. A protective device was designed to prevent the dent and collapse behaviors.